Queer Politics: Identity, Sexuality and Europe: „Queer“ политика: Идентитет, сексуалност и Европа - Gržinić, Marina; Jakimovska, Jana (Identities: Journal for Politics, Gender and Culture, 2003)
Author(s): Marina Gržinić | Марина Гржиниќ Title (English): Queer Politics: Identity, Sexuality and Europe Title (Macedonian): „Queer“ политика: Идентитет, сексуалност и Европа Translated by (English to Macedonian): Jana Jakimovska | Јана Јакимовска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 63-85 Page Count: 22 Citation (English): Marina Gržinić, “Queer Politics: Identity, Sexuality and Europe,” Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003): 63-85. Citation (Macedonian): Марина Гржиниќ, „‚Queer‘ политика: Идентитет, сексуалност и Европа“, превод од англиски Јана Јакимовска, Идентитети: списание за политика, род и култура, т. 2, бр. 2 (зима 2003): 63-85.